Exploring the Nonlinear Mechanical Characteristics of 3D-Printed ABS with Varying Infill Densities - Md Zisanul Haque Bhuiyan; Khalil Khanafer (Journal of Manufacturing and Materials Processing)
This study investigates the mechanical behavior of ASTM D638-02a standard uniaxial tensile test specimens fabricated from 3D-printed acrylonitrile butadiene styrene (ABS) using fused deposition modeling (FDM) with a grid infill pattern at varying densities of 20%, 40%, 60%, and 100%. The research aims to provide a deeper understanding of how infill density influences the mechanical properties of FDM-printed ABS, an area critical for optimizing structural performance in additive manufacturing applications. Experimental uniaxial tensile tests reveal that as the infill density increases from 20% to 60%, the strain at break decreases from 4.7% to 3.9%; however, at 100% infill, the strain at break rises to 5.8%. Meanwhile, the average Young’s modulus exhibits an exponential increase from 513.78 MPa at 20% infill to 2394.8 MPa at full density, indicating greater stiffness with higher infill. Due to the inherent nonlinear elastic deformation of 3D-printed ABS, this study further explores the material’s behavior through finite element analysis (FEA) using Ansys Mechanical. Four hyperelastic material models—Neo-Hookean, Mooney–Rivlin (two-parameter), Mooney–Rivlin (three-parameter), and Yeoh (third order)—were evaluated using inverse analysis to determine material constants. The results indicate that while all models exhibit good correlation with experimental data, the three-parameter Mooney–Rivlin and Yeoh models achieve the highest accuracy (higher R2 values) across all infill densities. However, the Neo-Hookean model, despite being a single-parameter approach, demonstrates a consistent trend where its parameter value increases with infill density. This study provides novel insights into the nonlinear elastic properties of 3D-printed ABS and establishes a foundation for selecting appropriate hyperelastic models to accurately predict mechanical behavior in FDM-printed structures.